Integrity Violations, White-Collar Crime, and Violations of Human Rights: Revealing the Connection. (1st October 2016) - Kolthoff, Emile
Abstract : This article reviews the findings of three research projects—all performed by the author and companions—supporting the hypothesis that integrity violations comprise white-collar crime or human rights violations or can be an indicator of more serious crime in an organization. Two of these studies have not previously been published in journals. Two of the projects compare observed integrity violations and ethical leadership in the United States with those in the Netherlands, Serbia, and Montenegro. The third study explores the connection between integrity violations and human rights violations by drawing the topic closer to the concept of state crime. Bridging the gap between public administration and criminology with a reflection on contributory factors to unethical behavior in the sense of white-collar crime, the article concludes with some coherent observations derived from the research projects discussed and encourages investment in ethics and integrity management as an instrument to prevent and control organizational crime and human rights violations.